2014
DOI: 10.1111/imj.12500
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone deficiency and quality of life in Australasian testicular cancer survivors: a prospective cohort study

Abstract: This is the first prospective study in a contemporary Australian/New Zealand population to determine the prevalence of testosterone deficiency in testicular cancer survivors at 12 months from treatment, and any association with poorer quality of life. Hormone assays from 54 evaluable patients in a prospective cohort study revealed biochemical hypogonadism in 18 patients (33%) and low-normal testosterone in 13 patients (24%). We found no association between testosterone levels and quality of life (all P > 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Conflicting evidence regarding associations with depression was found for ( a ) older age (significantly associated in 2 good and 1 poor studies, not associated in 1 good and 2 fair studies); ( b ) lower education (significantly associated in 1 good and 1 fair studies, not associated in 1 fair study); and ( c ) hormone levels (significantly associated in 1 poor study, not associated in 2 fair/poor studies).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Conflicting evidence regarding associations with depression was found for ( a ) older age (significantly associated in 2 good and 1 poor studies, not associated in 1 good and 2 fair studies); ( b ) lower education (significantly associated in 1 good and 1 fair studies, not associated in 1 fair study); and ( c ) hormone levels (significantly associated in 1 poor study, not associated in 2 fair/poor studies).…”
Section: Resultsmentioning
confidence: 97%
“…Two good studies using single items found 28% and 31% of TC survivors reported “quite a bit” or “very much” FCR 10 years postdiagnosis, although 1 fair study found FCR reduced from 45% at 6 months posttreatment to 12% at 4 years posttreatment, perhaps because of regular follow‐up during this time period. Fear of cancer recurrence prevalence estimates from 2 fair studies were also generally high (42‐45%) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study confirmed decreased levels of TST and increased levels of LH in patients with osteopenia/osteoporosis. Decreases in QoL have been attributed to the sequelae of hypogonadism, including fatigue, loss of libido, impaired fertility, weight gain, depression, and osteoporosis (O’Carrigan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of unmet supportive care needs varied within and between studies (see [15,23,36,37], anxiety [23,43,45,51,53,54,57], depression [23,39,43,45,54], fear of recurrence [23,37,38,41,59], and body image issues [15,32,37,38,52,58] were commonly experienced. Timely intervention for emotional support [23,32,37,59], coping with threats to masculinity [23,24,31] and counselling for issues about infertility were needed [32,33].…”
Section: Frequency Of Unmet Supportive Care Needsmentioning
confidence: 99%